Country Club, Trinidad, B.W.I. - (:unkn) unknown (My University, 2009)
A giant Samaan tree stands at the driveway and entrance of the Trinidad Country Club. Behind the hedge at right is a large hall for dining and dancing. Postcard numbered 19.
Colour: Coloured; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Clubs--Trinidad and Tobago; Trees--Trinidad and Tobago; Historic buildings--Trinidad and Tobago; Architecture--Trinidad and Tobago; Hanging baskets; Trinidad Country Club